INCIDENCE OF FREE THROWS IN PROFESSIONAL BASKETBALL GAMES - José Vicente García Tormo; Daniel Pérez Manzano; Alejandro Vaquera Jiménez; Juan Carlos Morante Rábago (Federación Extremeña de Balonmano; University of Extremadura, 2015)
The aim of this study is to describe the incident of the free throw on the final results of the basketball match, and see how other factors may influence the final average of successful free throws, comparing national leagues with European competition. A total of 59,364 free throws have been analyzed, corresponding to 1722 matches from two seasons of the Spanish professional basketball league (ACB and LFB) and European league (Euroleague Euroleague and women). Has been made descriptive analysis, an analysis of synchrony and an analysis of the residuals corrected. The results demonstrate the importance of free throws for the final score, especially in male and when is a close match. Likewise, the home court advantage is related to higher efficiency in free throws and win the match. Key words: